Career management for scientists and engineers - John K. Borchardt (American Chemical Society New York,Oxford University Press, 2000)
This book will be an important resource for both new graduates and mid-career scientists, engineers, and technicians. Through taking stock of existing or desired skills and goals, it provides both general advice and concrete examples to help assess a current job situation or prospect, and to effectively pursue and attain new ones. Many examples of properly adapted resumes and interview techniques, as well as plenty of practical advice about adaptation to new workplace cultural paradigms, such as team-based management, make this book an invaluable reference for the professional scientist in today's volatile job market